Pentingnya Peran Keluarga dalam Membentuk Mental dan Sikap Bela Negara pada Anak-anak - Ulfah, Audya; Kius, Florentina Sindhi (Jurnal Pendidikan Kewarganegaraan dan Politik, 2025)
Education in National Defense plays an essential role in shaping the character of the Indonesian nation, especially among the younger generation. This article examines the importance of national defense education within the context of a diverse society, as well as the involvement of all elements of the community in supporting such education. Through a literature review approach, the article discusses the legal foundations, concepts, objectives, and methods of national defense education, with a particular focus on early childhood. The family, as the child’s first environment, holds a crucial role in instilling national defense values from an early age. By emphasizing this aspect, it is expected that the young generation can grow into resilient individuals who are responsible for their nation and country.